2014
DOI: 10.1007/s00335-014-9530-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of atherosclerosis, obesity, and energy balance in consomic mice

Abstract: Metabolic diseases such as obesity and atherosclerosis result from complex interactions between environmental factors and genetic variants. A panel of chromosome substitution strains (CSSs) was developed to characterize genetic and dietary factors contributing to metabolic diseases and other biological traits and biomedical conditions. Our goal here was to identify quantitative trait loci (QTLs) contributing to obesity, energy expenditure and atherosclerosis. Parental strains C57BL/6 and A/J together with a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 67 publications
4
24
6
Order By: Relevance
“…2; Shao et al 2010;Yazbek et al 2011;DeSantis et al 2013;Kato et al 2014;Winawer et al 2014;Zhu and Matin 2014). The CSSs and congenic strains derived from CSSs have been used to map QTLs and identify causal genetic variants for traits such as body weight, glucose homeostasis, anxiety, hearing loss, bone morphology, blood clotting, liver fibrosis, energy expenditure, seizure susceptibility, among others (Singer et al 2004;Singer 2005;Winawer et al 2007;Gregorová et al 2008;Sa et al 2008;Shao et al 2008;Boell et al 2011;DeSantis et al 2013;Spiezio et al 2014;Street et al 2014). …”
Section: Chromosome Substitution Strains (Csss)mentioning
confidence: 99%
See 1 more Smart Citation
“…2; Shao et al 2010;Yazbek et al 2011;DeSantis et al 2013;Kato et al 2014;Winawer et al 2014;Zhu and Matin 2014). The CSSs and congenic strains derived from CSSs have been used to map QTLs and identify causal genetic variants for traits such as body weight, glucose homeostasis, anxiety, hearing loss, bone morphology, blood clotting, liver fibrosis, energy expenditure, seizure susceptibility, among others (Singer et al 2004;Singer 2005;Winawer et al 2007;Gregorová et al 2008;Sa et al 2008;Shao et al 2008;Boell et al 2011;DeSantis et al 2013;Spiezio et al 2014;Street et al 2014). …”
Section: Chromosome Substitution Strains (Csss)mentioning
confidence: 99%
“…As a result, CSSs can detect weaker and hence more QTLs than other resources given similar sample sizes. A striking example involves results from two recent studies (Logan et al 2013;Spiezio et al 2014). One study focused on behavioral traits in DO mice and the other on metabolic traits in CSSs.…”
Section: Mapped Qtlsmentioning
confidence: 99%
“…Previously, this diet was used as a metabolic challenge to evoke broad phenotypic responses in 43 inbred mouse strains, and to genetically map several metabolic phenotypes, including obesity, gut microbial composition, glucose homeostasis, dyslipidemia, hepatic steatosis, atherosclerosis and energy balance (SVENSON et al 2007;PARKS et al 2013;SPIEZIO et al 2014;SINASAC et al 2016). A recent study by Threadgill and colleagues compared the metabolic effects of the Western-style diet to a control diet, and three additional diets (Mediterranean, Japanese, and Maasai/ketogenic) in four mouse strains; A/J, C57BL/6J, FVB/NJ and NOD/ShiltJ (BARRINGTON et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…50,51 Genome surveys using a panel of chromosome substitution strains (CSSs) in which each C57BL/6J chromosome has been individually replaced with the corresponding A/J chromosome 52 showed that sequence variants on many chromosomes control susceptibility, with the effects of each acting in a highly non-additive manner. 53,54 For the majority of traits, the cumulative phenotypic effect (sum of the signed deviation from C57BL/6J) across all strains in the CSS panel was found to greatly exceed 100%, with an average cumulative effect of $800% across 90 blood, bone, and metabolic traits. 53 Similar results for 54 traits in a panel of rat CSSs argue that pervasive and strong non-additive effects may be a general genetic phenomenon.…”
Section: Modifiers Of Complex Traitsmentioning
confidence: 99%
“…The A/J allele of Obrq2 significantly decreases weight gain induced with a high-fat diet, but the magnitude of this effect depends on the genetic source (A/J or C57BL/6J) of multiple additional QTLs on the same chromosome. [53][54][55] In some cases, nearly complete protection from diet-induced obesity is found. Protection is lost, however, with various small changes in the strain origin of closely flanking chromosome segments.…”
Section: Modifiers Of Complex Traitsmentioning
confidence: 99%